Rancang Bangun Sistem Informasi Manajemen Berbasis Web untuk UKM Bandar Lampung Metode RAD - Doni Eko Hendro Pramono; Untoro Apsiswanto; Ridwan Yusuf (Journal of Technology and Data Science, 2025)
Small and Medium Enterprises (SMEs) in Bandar Lampung City are growing rapidly with 51,267 registered units dominated by the trade, culinary, and service sectors, yet most business actors still manage transaction and inventory data manually, making data-driven decision making difficult. This study designs and builds a web-based Management Information System supporting product, inventory, sales-purchase transactions, customer-supplier, and financial reporting management using the Rapid Application Development (RAD) method through four phases: Requirements Planning, User Design, Construction, and Cutover. The system was developed using the Laravel 11 framework with an MVC architecture, MySQL 8 database, and a Bootstrap 5 interface enhanced with Chart.js graphs. Functional testing using Black Box on 60 test cases produced 59 successes on the first run (98.33 percent) and 100 percent after fixing a single bug in the purchase transaction module. User Acceptance Testing involving 10 SME respondents from the culinary, trade, and service sectors yielded an average score of 4.28 out of 5 (85.6 percent) categorized as very good, with feature suitability achieving the highest score of 4.5. The system is designed as a foundation that can be integrated with the national digital platform SAPA UMKM being developed by the Ministry of MSMEs for 57 million business actors in Indonesia. The findings confirm the effectiveness of RAD for SME-scale system development with active user involvement from the start.